Bronchoscopic and bronchographic findings in 12 patients with sarcoidosis and severe or progressive airways obstruction. Issue 4 (April 1990) - Udwadia, Z F; Pilling, J R; Jenkins, P F; Harrison, B D
Abstract : Twelve patients (8 men), aged 33-67 (mean 49) years, with histologically proved sarcoidosis underwent bronchoscopy. All had symptoms, signs (wheeze in 11, high pitched inspiratory "squeaks" in six, stridor in three), and physiological abnormalities characteristic of severe or worsening airways obstruction. Eleven patients also underwent bronchography. At the time of bronchoscopy four patients had stage II, one stage III, and seven stage IV sarcoidosis. All patients had a peak expiratory flow (PEF) of 70% predicted or less and a maximum expiratory flow at 50% (MEF50) and 25% (MEF25) of vital capacity below 35% predicted. The ratio of their forced expiratory volume in one second to forced vital capacity (FEV1/FVC) ranged from 37% to 65%. Fibreoptic bronchoscopy showed single or multiple areas of segmental bronchial stenoses in 10 patients, two of whom had stenotic webs. Bronchography showed that the sites and severity of stenoses were more widespread than suspected from the bronchoscopic findings. Five of the 11 patients undergoing bronchography had bronchiectasis, which was restricted to the upper lobes in three and a lower lobe in one and affected both upper and lower lobes in one patient. The bronchiectasis had not been suspected or diagnosed from the chest radiography or the bronchoscopy.